Sikap Konsumen terhadap Atribut Produk untuk Mengukur Daya Saing Produk Jeruk - Agriani Hermita Sadeli; Hesty Nurul Utami (Faculty of Economics and Business, University of Pasundan, 2013)
This research aim is to discover Indonesian local orange competitiveness in Bandung City market based on consumer point of view through the comparison of consumer attitude on local orange and import orange product attribute. By applying descriptive survei method with quantitative data, this research employs 84 respondents, which is orange consumer in Bandung City. Consumer attitude model which apply in this research was being adapt for agribusiness product especially for orange. Consumers in Bandung City have a certain view that import orange is more supreme in almost every produt attribute dimension rather than local orange. Except for water content attribute, consumers think that local orange has water content as much as import orange. Consumers attitude towards import orange were a better flavor fragrance, a fresher, a better shape and color, a bigger size, a sweeter taste, and the last is it is cheaper than local orange. From this research it show that local orange competitiveness is still beneath import orange based on consumer view. This is a threat for local orange so that it necessary to make action plan from all the stakeholder which involve in local orange to increase the product quality standard of local orange to fullfil consumer needs and wants on local orange.